IMPLEMENTASI MAQASHID SYARI’AH SEBAGAI MODEL KEBIJAKAN KESEJAHTERAAN MASYARAKAT PEMERINTAH KOTA MALANG PERIODE 2011- 2016 - ANIS NI'AM IMANA (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
This study focuses on revealing the policies of social welfare development by using maqashid syari’ah namely: religion (di<n), reason (‘aql), soul (nafs), descent (nasl), and proverty (ma<l) as a model of regional welfare development in Malang city. The unfulfilled basic rights of economic needs will cause economic problems. The limitation of Human Development Index (HDI) in measuring human’s welfare is deemed inadequae due to the absence of spiritual welfare. This paper will discuss the application of maqashid al sharia as a model of Government’s policy development in Malang City. This study uses qualitative approach with data collect is performed through interviews, observation and documentation. The results of this study indicate that: 1) The public welfare development policies and strategies applied by the Malang Government are: a) The preservation of religion (h{ifz{u al- di>n): forming prosperous, religious and tolerant society, b) The preservation of mind (h{ifz{u al- ‘aql): creating educated society, c) Guarding the soul (h{ifz{u al- nafs): establising clean and healthy society and providing excellent public services, d) Preservation of hereditary (h{ifz{u al- nasl): child and pregnant women’s health counselling, e) Preservation of property (h{ifz{u al- ma<l): Improving regional economic sectors, creating tourism cities and building local infrastructure.